ANALISIS KEMAMPUAN MATEMATIS SISWA SMA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI SISTEM PERTIDAKSAMAAN LINEAR DUA VARIABEL - Jais, Ernawati; Usa, Suwarni La; Paisa, Nur (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2023)
The formulation of the problem in this research is how are high school student’ mathematical abilities in solving story problem on system of two variables linear inequalities? This research aims two analyze the mathematical abilities of high scool students in solving story problems on two-variable system of linear inequalities. This research uses descriptive research methods with a qualitative approach. The subjects in this research were 25 students of sman 1 pasarwajo science class v. Data collection in thi research was carried out using research instruments in the form of tests and interviews with students, to measure high school students’ mathematical abilities in story test through yhe material on the system of linear inequalities in two variables. Based on the research results, the following conclusions were obtained: (1) for problem solving abilities, it is known that in hihg ability subjects there are 16% of students, 24% in medium ability subjects, and 60% in low ability subjects. (2) For reasoning ability, it is known that in high ability subjects there are 4% of students, in medium ability subjcts there are 8%, and in low ability there are 88% of students. (3) For mathematical communication skills, it is known that in the high ability subject there are 4% of students, in the medium subject there are 24%, and in the low ability subject there are 72% of students. (4) For mathematical connection abilities in high ability subjects there are 16% of students, 20% of students in medium ability subjects, and 64% of students in low ability subjects. (5) For representational ability in high ability subjects there are 4% of students, in medium ability subjects there are 6% of students, and in low ability subjects there are 80% of students.